2003
DOI: 10.2460/javma.2003.223.670
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of prices paid for feeder calves sold at conventional auctions versus special auctions of vaccinated or conditioned calves in Ontario

Abstract: Results suggested that producers selling calves at special auctions at this market received a premium, compared with producers selling calves at conventional auctions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…7 Other common management procedures during preconditioning programs include castration of sexually intact males, dehorning, and treatment for internal and external parasites. 8 The preconditioning program used in this study confirmed the benefit of reduced health problems in the finishing phase in which none of the cattle were observed to have clinical signs of BRD. Also, there appeared to be protections against BVDV afforded to the cattle.…”
Section: Discussionsupporting
confidence: 59%
“…7 Other common management procedures during preconditioning programs include castration of sexually intact males, dehorning, and treatment for internal and external parasites. 8 The preconditioning program used in this study confirmed the benefit of reduced health problems in the finishing phase in which none of the cattle were observed to have clinical signs of BRD. Also, there appeared to be protections against BVDV afforded to the cattle.…”
Section: Discussionsupporting
confidence: 59%
“…There have been studies reporting on the economic benefit and disease reduction benefit to ‘preconditioned calves’. Calves vaccinated or conditioned and sold through special auctions received a premium compared to producers selling at conventional auctions, and vaccinated and conditioned calves were less likely to receive treatment for BRD in the first 28 days in the feedlot (Macartney et al, 2003a, b). A summary of certified health programs indicated that cattle from the certified health program when sold through livestock videotape auction service consistently yielded improved price and these increased over time (King et al, 2006).…”
Section: Prevention and Controlmentioning
confidence: 99%
“…Details of the auction market have been published, along with associations between sale price, sale type, and physical characteristics of the lots of calves auctioned. 8 Calves sold at special auctions held at this market during 1999 and 2000 were required to have received primary and booster doses, according to label recommendations, of killed-virus vaccines against IBR, BPI-3, BVD, and BRS viruses and vaccines against H somnus and M haemolytica. Booster vaccinations must have been given at least 2 weeks prior to auction and 2 to 4 weeks after the initial dose.…”
Section: Methodsmentioning
confidence: 99%
“…The initial cost for each calf entering the feedlot was estimated from a previous study. 8 The difference in mean body weight of conditioned calves, compared with control and vaccinated calves, reflected the longer period required to prepare conditioned calves for auction. For purposes of analysis, we assumed that conditioned calves would be purchased at least 45 days later than control and vaccinated calves and, therefore, would be approximately 40.5 kg (90 lb) heavier (assuming a mean weight gain of 0.9 kg/d [2 lb/d]).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation